2021
DOI: 10.3389/fgene.2021.675197
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Nomogram Based on DNA Methylation-Driven Genes for Patients With Ovarian Cancer

Abstract: Background: DNA methylation affects the development, progression, and prognosis of various cancers. This study aimed to identify DNA methylated-differentially expressed genes (DEGs) and develop a methylation-driven gene model to evaluate the prognosis of ovarian cancer (OC).Methods: DNA methylation and mRNA expression profiles of OC patients were downloaded from The Cancer Genome Atlas, Genotype-Tissue Expression, and Gene Expression Omnibus databases. We used the R package MethylMix to identify DNA methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…IRS2, ANGPTL4, TGFBI, LHX9, PC, and DDIT4 [ 23 ]. Zhou et al identified a DNA methylation-driven genes signature, including PON3, MFAP4, AKAP12, and BHMT2 [ 24 ]. Moreover, Zheng et al developed a risk stratification system based on glycolysis-related lncRNAs, including AC133644.2, CTD-2396E7.11, CTD-3065, J16.9, LINC00240, and TMEM254-AS1 [ 25 ].…”
Section: Exploring Clinical Benefit Of Signaturementioning
confidence: 99%
“…IRS2, ANGPTL4, TGFBI, LHX9, PC, and DDIT4 [ 23 ]. Zhou et al identified a DNA methylation-driven genes signature, including PON3, MFAP4, AKAP12, and BHMT2 [ 24 ]. Moreover, Zheng et al developed a risk stratification system based on glycolysis-related lncRNAs, including AC133644.2, CTD-2396E7.11, CTD-3065, J16.9, LINC00240, and TMEM254-AS1 [ 25 ].…”
Section: Exploring Clinical Benefit Of Signaturementioning
confidence: 99%
“…( 35 ), and the DNA methylation-driven gene signature established by Zhou et al. ( 36 ), as shown in Figure S2 .…”
Section: Resultsmentioning
confidence: 99%
“…As an important type of epigenetic modification, DNA methylation has been reported to participate in the process of disease occurrence, diagnosis, prognosis evaluation and treatment [10,22,39,40]. In OC, DNA methylation also shows value in prognostic evaluation, but the prediction efficiency is not particularly accurate, and whether there are other values remains unclear [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that DNA methylation status, as well as DNA methylationrelated genes, can be used in the diagnosis, treatment and prognosis of diseases [9][10][11]. Meanwhile, DNA methylation probes or methylation-related genes have also been reported for the prognostic assessment of OC [12,13]. However, the predictive efficacy of these methylation related models is not particularly accurate, and it is not clear whether there are other values in addition to the prognostic value.…”
Section: Introductionmentioning
confidence: 99%